Experimentální ověření dodatečného provádění otvoru do železobetonových stěn - Šimek, Ondřej; Zich, Miloš; Požár, Michal; Nečas, Radim (Vysoké učení technické v Brně,Fakulta stavební, 2021)
Předmětem článku je uvedení výsledků experimentů prefabrikovaných železobetonových stěn, do kterých byl dodatečně vyřezán otvor za současného působení zatížení. Jedná se o stěny, které simulují běžnou stěnu v panelovém domě, do které je dodatečně proveden otvor. Stěny jsou vyztuženy různými variantami: od jednoduchého vyztužení kari sítí, po vyztužení standartní výztuží po obvodě, v nadpraží i pilířích. Je tak studován i vliv tzv. „spící výztuže“, tj. výztuže, která je v panelu předem připravena pro případ dodatečného provedení otvoru. Je studován vliv této výztuže na rozvoj trhlin a změn poměrných přetvoření na panelu po vyřezání otvoru. V rámci experimentu je sledováno i dlouhodobé chování panelů s dodatečně provedeným otvorem.

The subject of the article is to present the results of experiments of prefabricated reinforced concrete walls that were loaded prior to the making of an additional opening. These are walls that simulate a regular wall in a wall panel building, into which an additional opening is made. The walls are reinforced with different variants of reinforcement: from simple reinforcement with wire mesh to standard reinforcement around the perimeter, in the lintel and the pillars. The influence of so called "sleeping reinforcement" is studied. This reinforcement is pre-prepared in the panel for the case of making an additional opening. The effect of this reinforcement on the development of cracks and changes in strain on the panel after making the additional opening is studied. Long term monitoring of the panels with newly made opening is also conducted as a part of the experiment.
Experimental Verification of Making an Additional Opening to the Reinforced Concrete Walls
Keywords: Železobetonová stěna; vyztužení; konstrukční zásady; dodatečný otvor; Reinforced-concrete wall; reinforcement; detailing of reinforcement; additional opening